Engrosamiento de la mucosa del seno maxilar y lesiones periapicales, estudio con tomografía de haz cónico, Iquitos 2017-2021 - Vasquez Oliveira, Gilson (2022)
The present investigation had as an objective to determine the relationship between the thickening of maxillary sinus mucosa and the presence of periapical lesions studied with cone beam CT in a virtual file, that had CTs from 2017-2021 period, of a private radiologic center in Iquitos, the sample was formed by 125 patients, in whom CT scans were made, (44% of masculine sex and 56% of feminine sex), of them 64% (80) were adults (27 to 59 years). The average age was 46,19 years (STD ±15,62 years), applying the inclusion and exclusion criteria, we observed 203 hemimaxilla (53,2% right side and 46,8% to the left side), the molar tooth was the most observed (88,2%) The periapical lesions were categorized according the CBCT-PAI y we observed 14,8% (30) of the total, and maxillary mucosa thickening was found in 51,2% (104) cases in total. 24.1% (49) of the maxillary mucosa thickening cases showed a thickening of 2.1 mm to 4.0 mm. 10.8% (22) of the cases in this sample presented periapical lesions and maxillary mucosa thickening. In conclusion, there exists a highly significant relationship between the maxillary sinus mucosa and the presence of periapical lesions. (p=0,009)